Urine and fecal excretion patterns of dairy cows divergent for milk urea nitrogen breeding values consuming either a plantain or ryegrass diet - C.J. Marshall; M.R. Beck; K. Garrett; G.K. Barrell; O. Al-Marashdeh; P. Gregorini (Journal of Dairy Science, 2022)
ABSTRACT: Environmental degradation has been attributed to inefficient nitrogen utilization from pastoral dairy production systems. This degradation has especially been associated with the urine patch, which has been identified as a key component of nitrate leaching to waterways. However, a lack of information exists regarding the pattern of urination events and individual urination characteristics across the day, which would help inform strategic management decisions. The aim of this study was therefore to evaluate and report the patterns and characteristics of fecal and urination events throughout the day for cows divergent for milk urea nitrogen breeding values (MUNBV) on either a plantain [Plantago lanceolata L. (PL)] or ryegrass [Lolium perenne L. (RG)] diet as ways to reduce environmental impact. Sixteen multiparous lactating Holstein Friesian × Jersey cows divergent for MUNBV were housed in metabolism crates for 72 h, with all excretion events captured and analyzed. Cows selected as low for MUNBV consistently had a 65.2-kg lower urinary urea nitrogen (UUN) load (kg/ha) than high MUNBV cows for all hours of the day when consuming RG. The association between lower urinary urea loading rates and less N leaching implies a reduced environmental impact from low MUNBV cows consuming RG. When cows consumed PL, regardless of MUNBV, they had on average a 137.5-kg (UUN/ha) lower loading rate compared with high MUNBV cows on RG and a 72.2-kg (UUN/ha) lower loading rate compared with low MUNBV cows consuming RG across the day. Cows on PL also exhibited a different diel pattern of UUN load compared with cows consuming RG. Differences in the diel pattern of N excreted in feces were also detected based on MUNBV and by diet, with low MUNBV cows excreting on average 3.06 g more N in feces per event for the majority of the day compared with high MUNBV cows when consuming RG. Lower UUN loading rates and more N excreted in feces indicate a potentially lower environmental impact from low MUNBV cows when consuming RG compared with high MUNBV cows. The use of the PL diet also resulted in lower UUN loading rates and greater levels of N excreted in feces compared with RG, therefore also indicating its ability to reduce environmental impact compared with RG.